Perjanjian Perkawinan dalam Hukum Islam dan Persepsi Masyarakat Kelurahan Jelekong Kabupaten Bandung - Silma Kaffah Milati; Titin Suprihatin; Ilham Mujahid (Bandung Conference Series: Islamic Family Law, 2023)
Abstract. Marriage agreements in Islamic law based on Q.S Al-Maidah verse 1 and the hadith narrated by At-Tirmidhi, the law of the agreement is permissible. The Marriage Agreement has been regulated in Law No. 1 of 1974 and the Compilation of Islamic Law. However, in practice until now the people of the Jelekong Village have not made a marriage agreement. The purpose of this study was to find out the concept of a marriage agreement in Islamic law, the perception of the Jelekong Village community towards the marriage agreement and to find out the results of the analysis of the Jelekong Village community's perception of the marriage agreement in Islamic law. This study uses an empirical and sociological juridical approach. Primary data sources are the results of interviews and questionnaires while secondary data sources are obtained from books, journals and other supporting documents that are relevant to this research. The results of this study are marriage agreements in Islamic law, namely an agreement entered into by the prospective bride or husband and wife made before or during or throughout the marriage with their respective agreements and without coercion. Making a marriage agreement in Islamic law is permissible (mubah). Many people in the Jelekong Village still disagree with the marriage agreement, the perception of the Badung Village community regarding the marriage agreement is not in accordance with Islamic law. Abstrak. Perjanjian perkawinan dalam hukum Islam berdasarkan Q.S Al-Maidah ayat 1 dan hadis yang diriwayatkan oleh At-Tirmidzi hukum perjanjian itu diperbolehkan. Perjanjian Perkawinan telah diatur di dalam Undang-Undang No 1 Tahun 1974 dan Kompilasi Hukum Islam. Namun, dalam praktiknya sampai saat ini masyarakat Kelurahan Jelekong tidak ada yang membuat perjanjian perkawinan. Tujuan penelitian ini untuk mengetahui konsep perjanjian perkawinan dalam hukum Islam, persepsi masyarakat Kelurahan Jelekong terhadap perjanjian perkawinan dan mengetahui hasil analisis persepsi masyarakat Kelurahan Jelekong terhadap perjanjian perkawinan dalam hukum Islam. Penelitian ini menggunakan pendekatan yuridis empiris dan sosiologis. Sumber data primer yaitu diperoleh hasil wawancara dan kuisioner sedangkan sumber data sekunder diperoleh dari buku, jurnal, dan dokumen penunjang lainnya yang relevan dengan penelitian ini. Hasil penelitian ini adalah perjanjian perkawinan dalam hukum Islam yaitu suatu perjanjian yang dilakukan oleh calon pengantin atau suami dan istri yang dilakukan sebelum atau pada saat atau sepanjang perkawinan dengan kesepakatan masing-masing dan tanpa paksaan. Membuat perjanjian perkawinan di dalam hukum Islam diperbolehkan (mubah). Masyarakat Kelurahan Jelekong masih banyak yang tidak setuju dengan perjanjian perkawinan, persepsi masyarakat kelurahan jelekong terhadap perjanjian perkawinan tidak sesuai dengan hukum Islam.